The role of message-sequences in the sustainability of an online support community for older people - Pfeil, Ulrike; Zaphiris, Panayiotis; Wilson, Stephanie (My University, 2010)
This article presents an investigation of an online support community for older people, analyzing a data-set of messages posted over the period of six years. We studied messages that are related to each other which we call "message-sequences". We investigated the content of message-sequences and linked our findings to the level of activity of the online support community over time. We show how certain sequences of messages within the online community are related to the level of activity thus providing valuable insight into the role of message-sequences in sustaining online support communities for older people. We conclude that the mutual exchange of personal information and receiving support after talking about personal problems are basic components for the sustainability of the online community, whereas conversations that go off the topic of the online community seem to be related to a decrease in the level of activity.
Keywords: Older people; Online support community; Sustainability